A rapid Fourier transform infrared spectroscopic method for the determination of 2-TBARS in palm olein - Setiowaty, G.; Che Man, Y. B. (Elsevier B.V, 2003)
A rapid, simple, and environmentally friendly Fourier transform infrared (FTIR) spectroscopic method has been developed to directly determine 2-thiobarbituric acid reactive substances (TBARS) in palm olein. Two multivariate methods, partial least squares (PLS) and principal component regression (PCR), were used to build the calibration models that correlate the chemical 2-TBARS values to the selected spectral regions of FTIR data. The calibration models obtained were cross-validated with 'leave-one-out' method before applying to predict the TBARS values in palm olein. However, the calibration models obtained from the PLS method gave lower standard errors of prediction (SEP) compared to PCR. With the spectrometer calibrated, the predicted 2-TBARS results could be obtained within 5 min per sample, a major improvement over the conventional wet chemical method. © 2002 Elsevier Science Ltd. All rights reserved.